Exploring the mediating role of social support in sports participation and academic burnout among adolescent students in China - Jia Gao; Xiaodong Tian; Hailong Wu (Frontiers in Psychology)
IntroductionAcademic burnout among adolescent students has been a hot topic of concern among scholars. With the increase of academic pressure, the problem of academic burnout among adolescent students has become more and more prominent, which has a profound impact on their psychological health and academic performance. However, the relationship between sports participation and academic burnout among Chinese adolescent students and its underlying mechanisms remain to be investigated.MethodsThe present study aimed to investigate the relationship between sports participation and academic burnout among adolescent students and to verify the mediating role of social support between the two. In addition, this study used a non-probability convenience sampling technique to investigate the current status of sports participation, academic burnout, and social support among 1,267 Chinese adolescent students.ResultsThe results showed that male students scored slightly higher than female students in the sports participation and academic burnout tests, and slightly lower than female students in all social support tests. There was a negative correlation between sports participation and academic burnout among adolescent students (r = −0.62). There was a significant negative predictive effect between sports participation and academic burnout among adolescent students (β =−0.201, p < 0.05) and a positive predictive effect with social support (β = 0.231, p < 0.05). Social support had a negative predictive effect with academic burnout in adolescent students (β =−0.179, p < 0.05). Social support had a signiffcant mediating effect between sports participation and academic burnout among adolescent students (β =−0.349, p < 0.05).ConclusionThe results of this study provide valuable insight into educational interventions to mitigate and prevent academic burnout among adolescent students.